Inhibitory Effect of Propolis on Platelet Aggregation In Vitro. (10th October 2017) - Zhang, Yun-Xiang; Yang, Ting-Ting; Xia, Liu; Zhang, Wei-Fen; Wang, Jia-Fu; Wu, Ya-Ping
Abstract : Platelet hyperactivity plays an important role in arterial thrombosis and atherosclerosis. The present study was aimed to investigate the effects of different extracts of propolis and components of flavonoids on platelet aggregation. Platelet-rich plasma was prepared and incubated in vitro with different concentrations of the tested extracts and components of flavonoids. Platelets aggregation was induced by different agonists including adenosine diphosphate (ADP, 10  μ M), thrombin receptor activator peptide (TRAP, 50  μ M), and collagen (5  μ g/mL). At 25 mg/L to 300 mg/mL, the water extract propolis (WEP) inhibited three agonists-induced platelet aggregations in a dose-dependent manner. The flavonoids isolated from the propolis also showed markedly inhibited platelet aggregation induced by collagen, ADP, and TRAP, respectively. The components including caffeic acid phenethyl ester (CAPE), galangin, apigenin, quercetin, kaempferol, ferulic acid, rutin, chrysin, pinostrobin, and pinocembrin and their abilities of inhibiting platelet aggregation were studied. It was concluded that propolis had an antiplatelet action in which flavonoids were mainly implicated.